My Brand, My Creation: The Mediating Role of Psychological Ownership in the Relationship between Co-Creation and Loyalty: My Brand, My Creation: Peran Mediasi Kepemilikan Psikologis dalam Hubungan antara Co-Creation dan Loyalitas - Bustam Bustam; Asriadi Asriadi (International Journal of Economic Entrepreneurship and Business Management, 2026)
This study aims to examine the mediating role of psychological ownership in the relationship between co-creation and value-driven brand loyalty in digital platform users in Indonesia. Using a causal-correlational quantitative design, data was collected through purposive sampling techniques  from active users of digital platforms who customized features, and then analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that co-creation had a positive and significant effect on brand loyalty (β = 0.230, p < 0.001) and psychological ownership (β = 0.455, p < 0.001). Furthermore, psychological ownership had a positive effect on brand loyalty (β = 0.347, p < 0.001) and was shown to play a complementary role in  the relationship between co-creation and brand loyalty (β = 0.158, p < 0.001). These findings prove that psychological ownership serves as an emotional bridge that converts the cognitive capital and effort of users during co-creation into long-term loyalty that is resistant to price wars, while minimizing the risk of perceived unpaid labor. Digital platform developers are advised to design customization features that provide real control to reinforce the user's sense of belonging.